Factors associated with maternal mortality in Sub-Saharan Africa: an ecological study - Alvarez, Jose Luis (BioMed Central, 2009)
BACKGROUND: Maternal health is one of the major worldwide health challenges. Currently, the unacceptably high levels of maternal mortality are a common subject in global health and development discussions. Although some countries have made remarkable progress, half of the maternal deaths in the world still take place in Sub-Saharan Africa where little or no progress has been made. There is no single simple, straightforward intervention that will significantly decrease maternal mortality alone; however, there is a consensus on the importance of a strong health system, skilled delivery attendants, and women's rights for maternal health. Our objective was to describe and determine different factors associated with the maternal mortality ratio in Sub-Saharan countries. METHODS: An ecological multi-group study compared variables between many countries in Sub-Saharan Africa using data collected between 1997 and 2006. The dependent variable was the maternal mortality ratio, and Health care system-related, educational and economic indicators were the independent variables. Information sources included the WHO, World Bank, UNICEF and UNDP. RESULTS: Maternal mortality ratio values in Sub-Saharan Africa were demonstrated to be high and vary enormously among countries. A relationship between the maternal mortality ratio and some educational, sanitary and economic factors was observed. There was an inverse and significant correlation of the maternal mortality ratio with prenatal care coverage, births assisted by skilled health personnel, access to an improved water source, adult literacy rate, primary female enrolment rate, education index, the Gross National Income per capita and the per-capita government expenditure on health. CONCLUSIONS: Education and an effective and efficient health system, especially during pregnancy and delivery, are strongly related to maternal death. Also, macro-economic factors are related and could be influencing the others.